Persepsi Siswa Kelas X MIPA 2 SMA Negeri 1 Tawangsari terhadap Metode Pembelajaran Berbasis Online dimasa Pandemi - Suwarto Suwarto; Sri Wahyuni; Sri Yamsih (Universitas PGRI Semarang, 2021)
This research was conducted with the aim of knowing the perceptions of students of class X MIPA 2 SMA Negeri 1 Tawangsari towards online-based learning methods. After the outbreak of the corona virus which has become a boomerang for various countries, learning for school students is carried out online from home. Opinion observation method is used as a method to analyze data in order to complete the research using a sample of 30 students of class X MIPA 2 SMA Negeri 1 Tawangsari. There are several categories that need to be considered in the research results. The categories that were considered were: learning materials, student interaction with teachers and students with other students, and learning atmosphere. So this research focuses on how students respond to online learning (online).